Pelestarian Tekuluk Sebagai Warisan Budaya Melayu Jambi - Fatonah, Fatonah; Hudaya, Padhil; Defrianti, Denny; Lestari, Inda; Rahman, Abd (Penerbit Widina, Widina Media Utama, 2024)
This community service activity aims to preserve Jambi Malay culture through the use of tekuluk, a traditional head covering rich in cultural and philosophical values. Tekuluk, as a symbol of Jambi Malay women's identity, is now rarely used, especially by the younger generation. This program was implemented in Kelurahan Muara Jangga, Kecamatan Batin XXIV, Kabupaten Batanghari, which has experienced a decline in the use of tekuluk in the daily lives of its people. The approach used was socialization and training for the community, especially young people, about the meaning, history, and how to use tekuluk in everyday life and traditional events. In addition, this program also promoted the adaptation of tekuluk in modern fashion trends so that it would be more popular with the younger generation. The results of the activity showed an increase in public awareness of the importance of preserving tekuluk as part of cultural heritage, as well as the emergence of interest among the younger generation to wear tekuluk again on various occasions. By using participatory and collaborative methods, this program is expected to contribute to the preservation of Jambi Malay culture in a sustainable manner and as an effort to popularize the use of Jambi tekuluk in the community, especially the younger generation in Kelurahan Muara Jangga through one of the tri daharma activities of higher education in community service.ABSTRAKKegiatan pengabdian masyarakat ini bertujuan untuk melestarikan budaya Melayu Jambi melalui penggunaan tekuluk, penutup kepala tradisional yang kaya akan nilai budaya dan filosofi. Tekuluk, sebagai simbol identitas perempuan Melayu Jambi, kini semakin jarang digunakan, terutama oleh generasi muda. Program ini dilaksanakan di Kelurahan Muara Jangga, Kecamatan Batin XXIV, Kabupaten Batanghari, yang mengalami penurunan penggunaan tekuluk dalam keseharian masyarakatnya. Pendekatan yang digunakan adalah sosialisasi dan pelatihan kepada masyarakat, khususnya kaum muda, tentang makna, sejarah, dan cara penggunaan tekuluk dalam kehidupan sehari-hari dan acara adat. Selain itu, program ini juga mempromosikan adaptasi tekuluk dalam trend busana modern agar lebih diminati generasi muda. Hasil kegiatan menunjukkan adanya peningkatan kesadaran masyarakat akan pentingnya pelestarian tekuluk sebagai bagian dari warisan budaya, serta munculnya minat generasi muda untuk mengenakan tekuluk kembali dalam berbagai kesempatan. Dengan menggunakan metode partisipatif dan kolaboratif, program ini diharapkan dapat berkontribusi pada pelestarian budaya Melayu Jambi secara berkelanjutan dan sebagai salah satu upaya memasyarakatkan pemakaian tekuluk Jambi pada masyarakat khususnya generasi muda di kelurahan Muara Jangga melalui kegiatan salah satu tri dharma perguruan tinggi dalam pengabdian pada masyarakat.